Implementation of Distance Learning and Assessment in Kindergarten in Emergency Circumtances - Purnamasari, Nina; Heru, Anggraeni; Herawati, Fera (Indonesian Journal of Educational Assessment, 2020)
This study aims to get a clearer picture of distance learning (DL) in kindergarten and its assessment, to provide recommendations for policy options related to DL in kindergarten to optimizing students' development and abilities in the emergency. This study was randomly sampling subjects, which are principals, teachers, and parents who had kindergarten-age children. The data collection was through interviews, documentation, and questionnaires deployed by Google form. The results of this study showed that the best format of DL in kindergarten is blended. The assessment for this blended learning that can be done both by teacher and parents are by using communication forum and checklist sheets. Policy options for DL in kindergarten are the use of package modules/books, home visits, activity sheets, television and radio, and the coordination of the government at central and regional administration, and education stakeholders. These policy options become necessary because of the quality of DL based on the knowledge and skills of the teacher/parents that corresponds to the child's developmental stage. DL in kindergarten is the fulfillment of education rights to children in any circumstances. This effort optimizing the children's development of abilities and potential as expected